Acute fluoxetine treatment increases aggressiveness in juvenile matrinxã (Brycon amazonicus) - Wolkers, Carla Patricia Bejo [UNESP]; Serra, Mônica [UNESP]; Barbosa Júnior, Augusto; Urbinati, Elisabeth Criscuolo [UNESP] (Springer Nature, 2017)
Fluoxetine (FLX) is a selective serotonin (5-HT) reuptake inhibitor known for its effects modifying aggressiveness, personality traits, and anxiety-like behaviors. The aim of the present study was to evaluate the influence of the acute treatment, by immersion, with FLX on aggressive behavior of resident Brycon amazonicus fish. Fish pretreated with FLX presented an increase in aggressiveness, evidenced by the increase on the number of bites and chases against the intruder and a decrease in latency for the first attack, when compared to control fish. Together with previous studies, these results show the complexity of the neural modulation of the aggressive behavior in fish by 5-HTergic system.
Keywords: Aggressive behavior; Fish; Fluoxetine; Serotonin